PENGARUH DISIPLIN TERHADAP KINERJA KERJA PEGAWAI PADA BALAI BESAR KONSERVASI SUMBER DAYA ALAM (KSDA) PAPUA BARAT - Susana Magdalena Welly Muskita; Yerryynaldo Loppies (Soso-Q : Jurnal Manajemen, 2019)
Civil Servants as government servants and public servants are required to show performance and provide an optimal role in national development. Good employee performance with a high work ethic will help agencies to be able to meet the agency's targets, whereas if employee performance decreases and is bad it will harm the agency. The purpose of this study is to find out and analyze the effect of discipline on employee work performance at the Balai Great Conservation of Natural Resources (KSDA) of West Papua. This research method is a quantitative method. The population used is employees to find out and analyze the effect of discipline on employee work performance at the West Papua Natural Resources Conservation Center (KSDA). The sample used was employees to find out and analyze the effect of discipline on the work performance of employees at the West Papua Natural Resources Conservation Center (KSDA) with 42 people. The result of this research is that there is a significant influence between discipline and employee performance in knowing and analyzing the influence of discipline on the work performance of employees at the West Papua Natural Resources Conservation Center (KSDA), it can be seen from the partial test results (t test), resulting t - count 5,290> t-table 1,683, meaning that it is significant (df1 = 2 - 1 = 1 and df2 = 42 - 2 = 40). Significant here means that the Hypothesis is accepted. That is, because t-count> t-table. Keywords: Discipline and Work Performance